2016
DOI: 10.1016/j.semarthrit.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences for total knee replacement surgery: Relationship to clinical outcomes and stability of patient preferences over 2 years

Abstract: Objective Evaluate the relationship between patient preferences for total knee replacement (TKR) with receipt of TKR, and assess participant characteristics that may influence change in willingness to undergo TKR Methods Structured interviews of knee osteoarthritis (OA) patients were conducted. Logistic regression models were conducted to assess the association between baseline willingness and eventual receipt of TKR, adjusted for sociodemographic and clinical variables. Mixed models for repeated measures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The sample was predominantly white (93.5%), and previous literature demonstrates that decisions regarding willingness to undergo surgery may differ between races. [38][39][40][41] Vina et al 41 found that the decline in the willingness to operate, relative to baseline, was less in those who consulted with an orthopedic surgeon. In this study, just 58.9% of the sample spoke with an orthopedic surgeon about their knee, and our analysis does not reveal how this may have influenced patient responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample was predominantly white (93.5%), and previous literature demonstrates that decisions regarding willingness to undergo surgery may differ between races. [38][39][40][41] Vina et al 41 found that the decline in the willingness to operate, relative to baseline, was less in those who consulted with an orthopedic surgeon. In this study, just 58.9% of the sample spoke with an orthopedic surgeon about their knee, and our analysis does not reveal how this may have influenced patient responses.…”
Section: Discussionmentioning
confidence: 99%
“…As the condition is progressive, patients with knee OA are aware that arthroplasty is an inevitable long-term outcome 35,39,41,42 ; therefore, as the severity of their symptoms worsens, they may alter their opinions of or reassess the benefits and risks of undergoing surgery. Another important consideration when evaluating patients for treatment is that the level of pain does not always correlate with the structural severity of OA.…”
Section: Discussionmentioning
confidence: 99%
“…Due to ethical considerations, long term PHI data on TKRs post program was unavailable as the control group was not maintained. A review of the literature found only 2 studies that examined this relationship [5,14] and the transferability of these studies were deemed likely to be low due to considerations around participant access to surgery and individual engagement with personal health. Given the lack of progression to surgery data, the probability of surgery given a participant's willingness status was treated as an uncertain parameter.…”
Section: Methodsmentioning
confidence: 99%
“…In the study design for post-marketing approval which uses observational outcomes such as time-to-event of joint replacement surgery, considerable barriers exist in terms of need for large sample sizes due to low annual incidence rates (1.6–11.9%), 14 long study follow-ups (>5 years at least), 46 and the impact of non-disease and other subjective factors on the outcome (ie, comorbidities and/or age of the patient, costs, insurance cover, etc.). 168 , 169 There is a lack of universal consensus criteria for guiding patient recommendations regarding joint replacement surgery, leading to differences even among treatment centres within the same region. These issues need to be adequately addressed by study design.…”
Section: Perspectivesmentioning
confidence: 99%